Let the evidence speak again! Financial incentives are more effective than we thought. (July 2015) - Shaw, Jason D.; Gupta, Nina
<x xml:space="preserve">Abstract</x> In this essay, the authors rejoin the debate about financial incentive effectiveness. They (a) briefly review the state of the literature in 1998, (b) highlight new meta‐analytic findings and update conclusions regarding the financial incentives–performance relationship, (c) address the myth that financial incentives erode intrinsic motivation, (d) provide explanations for the presumed failure of financial incentives and (e) offer some concluding thoughts and suggestions for future research.